Evaluating the success of a marine protected area: A systematic review approach. (1st December 2016) - Gallacher, J.; Simmonds, N.; Fellowes, H.; Brown, N.; Gill, N.; Clark, W.; Biggs, C.; Rodwell, L.D.
Abstract: Marine Protected Areas (MPAs), marine areas in which human activities are restricted, are implemented worldwide to protect the marine environment. However, with a large proportion of these MPAs being no more than paper parks, it is important to be able to evaluate MPA success, determined by improvements to biophysical, socio-economic and governance conditions. In this study a systematic literature review was conducted to determine the most frequently used indicators of MPA success. These were then applied to a case study to demonstrate how success can be evaluated. The fifteen most frequently used indicators included species abundance, level of stakeholder participation and the existence of a decision-making and management body. Using the indicator framework with a traffic light system, we demonstrate how an MPA can be evaluated in terms of how well it performs against the indicators using secondary data from the literature. The framework can be used flexibly. For example, where no MPA data currently exist, the framework can be populated by qualitative data provided by local stakeholder knowledge. This system provides a cost-effective and straightforward method for managers and decision-makers to determine the level of success of any MPA and identify areas of weakness. However, given the variety of motivations for MPA establishment, this success needs to be determined in the context of the original management objectives of the MPA with greater weighting being placed on those objectives where appropriate. Highlights: A systematic review of indicators of success of marine protected areas. A list of most frequently cited biophysical, socio-economic and governance indicators. A demonstration of a case study application of evaluation of MPA success using a traffic light system of indicators. A framework of indicators for application to evaluate success of any MPA.